PENGARUH PERTUMBUHAN EKONOMI, INFLASI, DAU, DAN TRADE OPEN TERHADAP KETIMPANGAN PENDAPATAN RUMAH TANGGA DI BALI - Kardita, A. A. Gede Dirga; Setiawina, Nyoman Djinar; Budiasa, I Gede Sujana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
Problems in economic development are increased growth, reduced household income gaps, and poverty alleviation. However, it becomes a dilemma in developing countries where an increase in economic growth will increase the inequality of household incomes. The phenomenon in Bali, from 1996 to 2015 Bali's economic growth tends to increase. Inflation in Bali is stable, general allocation (DAU) in Bali always increases, and Trade open Bali is 7% to 11% from 1996 to 2015. On the other hand, the increasing of macro indicator in Bali is also followed by the increase of household income imbalance . This study aims to analyze the effect of DAU, inflation, economic growth, and trade open partially on income inequality in Bali, and to analyze the influence of each independent variable namely DAU (X1), inflation (X2), economic growth (X3) and trade open (X4), to the inequality of household income in Bali. Based on the results of the study only trade open is not singnifikan against Variable Y.